Assessing the Impact of Artificial Intelligence Tools on Reading Proficiency among Undergraduate Students of Prince Abubakar Audu University Anyigba, Kogi State Nigeria (Federal University Gusau Faculty of Education Journal, 2026)
Reading proficiency is a fundamental skill in higher education, yet many undergraduate students in Nigeria struggle with comprehension due to limited support and outdated instructional methods. The integration of artificial intelligence (AI) tools into education offers new possibilities for personalized and adaptive learning, but little research has examined their specific impact on reading development in Nigerian undergraduate settings. This study explores the perception and experiences of undergraduate students regarding the use of AI tools such as chatgpt, Rewordify and Read theory for enhancing students’ academic reading proficiency. Using a qualitative research approach, semi-structured interviews were conducted with eighty students from diverse disciplines who had prior exposure to AI tools. The thematic analysis framework was used to identify key themes across participant responses. Emerging themes included personalized and self-paced learning, vocabulary support and comprehension, increased engagement, and provision academic confidence. However, challenges such as over reliance on AI generated content, inconsistent usage habit, and digital literacy gaps were also identified. Finding suggested that AI tools, implemented with appropriate guidance, equitable access, and curriculum alignment, can significantly enhanced students’ reading confidence, comprehension, and motivation. The study contributed to the body of literature on AI in education by offering context-specific insight for technology integration in literacy instruction. It highlighted the need for inclusive, students centered strategy to promote reading proficiency in resource-constrained academic environment. Future research should explore teachers respective, long-term learning outcomes, and the integration of AI tools across diverse linguistic and institutional contexts to further validate and expand on these findings.